808 nm driven Nd3+-sensitized upconversion nanostructures for photodynamic therapy and simultaneous fluorescence imaging. Issue 1 (18th November 2014) - Wang, Dan; Xue, Bin; Kong, Xianggui; Tu, Langping; Liu, Xiaomin; Zhang, Youlin; Chang, Yulei; Luo, Yongshi; Zhao, Huiying; Zhang, Hong
Abstract : The novel nanostructures have been designed to balance the robustness of the upconversion emission and the FRET efficiency for image-guided photodynamic therapy under triggering of 808 nm light. Abstract : The in vivo biological applications of upconversion nanoparticles (UCNPs) prefer excitation at 700–850 nm, instead of 980 nm, due to the absorption of water. Recent approaches in constructing robust Nd 3+ doped UCNPs with 808 nm excitation properties rely on a thick Nd 3+ sensitized shell. However, for the very important and popular Förster resonance energy transfer (FRET)-based applications, such as photodynamic therapy (PDT) or switchable biosensors, this type of structure has restrictions resulting in a poor energy transfer. In this work, we have designed a NaYF4 :Yb/Ho@NaYF4 :Nd@NaYF4 core–shell–shell nanostructure. We have proven that this optimal structure balances the robustness of the upconversion emission and the FRET efficiency for FRET-based bioapplications. A proof of the concept was demonstrated for photodynamic therapy and simultaneous fluorescence imaging of HeLa cells triggered by 808 nm light, where low heating and a high PDT efficacy were achieved.